Animals devoid of pulmonary system as infection models in the study of lung bacterial pathogens - López Hernández, Yamilé; Yero, Daniel; Pinos-Rodríguez, Juan M.; Gibert, Isidre (Frontiers in Microbiology, 2015)
Biological disease models can be difficult and costly to develop and use on a routine basis. Particularly, in vivo lung infection models performed to study lung pathologies use to be laborious, demand a great time and commonly are associated with ethical issues. When infections in experimental animals are used, they need to be refined, defined, and validated for their intended purpose. Therefore, alternative and easy to handle models of experimental infections are still needed to test the virulence of bacterial lung pathogens. Because non-mammalian models have less ethical and cost constraints as a subjects for experimentation, in some cases would be appropriated to include these models as a valuate tools to explore host-pathogen interactions. Numerous scientific data have been argued to the more extensive use of several kinds of alternative models, such as, the vertebrate zebrafish (Danio rerio), and non-vertebrate insects and nematodes (e.g. Caenorhabditis elegans) in the study of diverse infectious agents that affect humans. Here we review the use of these vertebrate and non-vertebrate models in the study of bacterial agents, which are considered the principal causes of lung injury. Curiously none of these animals have a respiratory system as in air-breathing vertebrates, where respiration takes place in lungs. Despite this fact, with the present review we sought to provide elements in favour of the use of these alternative animal models of infection to reveal the molecular signatures of host-pathogen interactions.